Calculation of Unknown Preoperative K Readings in Postrefractive Surgery Patients. (11th February 2018) - Rosa, Nicola; De Bernardo, Maddalena; Borrelli, Maria
Abstract : Purpose . To determine the unknown preoperative K readings (Kpre) to be used in history-based methods, for intraocular lens (IOL) power calculation in patients who have undergone myopic photorefractive keratectomy (PRK). Methods . A regression formula generated from the left eyes of 174 patients who had undergone PRK for myopia or for myopic astigmatism was compared with other methods in 168 right eyes. The Pearson index and paired t -test were utilized for statistical analysis. Results . The differences between Kpre and those obtained with the other methods were as follows: 0.61 ± 0.94 D (range: −3.94 to 2.05 D, p < 0.01 ) subtracting the effective treatment, 0.01 ± 0.86 D (range: −2.61 to 2.34 D, p = 0.82 ) with Rosa's formula, −0.02 ± 1.31 D (range: −3.43 to 3.68 D, p = 0.82 ) with the current study formula, and −0.43 ± 1.40 D (range: −3.98 to 3.12 D, p < 0.01 ) utilizing a mean K (Km) of 43.5 D. Conclusions . These formulas may permit the utilization of history-based methods, that is, the double-K method in calculating the IOL power following PRK when Kpre are unknown.